An Approximation Technique for Fractional Order Delay Differential Equations - Odetunde, Olutunde Samuel; Taiwo, Abass Ishola; Dehinsilu, Olusola Adebanwo (Iraqi Journal of Science, 2019)
In this research article, an Iterative Decomposition Method is applied to approximate linear and non-linear fractional delay differential equation. The method was used to express the solution of a Fractional delay differential equation in the form of a convergent series of infinite terms which can be effortlessly computable.The method requires neither discretization nor linearization. Solutions obtained for some test problems using the proposed method were compared with those obtained from some methods and the exact solutions. The outcomes showed the proposed approach is more efficient and correct.